Efektivitas Isolat Lokal Trichoderma sp. dalam Menekan Perkembangan Nematoda Bengkak Akar (Meloidogyne spp.) pada Tomat: Efficacy of Local Trichoderma sp. Isolates for the Suppression of Root-Knot Nematodes (Meloidogyne spp.) in Tomato - Dahlan, Yusnetti; Winarto; Darnetty (DINAMIKA PERTANIAN, 2026)
Background: Tomato (Lycopersicum esculentum Mill.) is a high-value horticultural commodity, but its cultivation is constrained by root-knot nematodes (Meloidogyne spp.). Biological control using antagonistic fungi Trichoderma spp. is an environmentally friendly alternative; however, the utilization of local isolates from West Sumatra remains limited. Objective: This study aimed to screen local Trichoderma spp. isolates from West Sumatra for their effectiveness in suppressing Meloidogyne spp. on tomato plants. Methods: The research was conducted from May to September 2022 using a completely randomized design with 4 treatments (control, Salimpaung isolate, Sungai Nanam isolate, and Tabek Patah isolate) and 6 replications. Trichoderma was applied (9 g/kg soil) one week before planting, followed by nematode egg infestation (±1000 eggs/polybag) one week after planting. Parameters observed at 45 days after infestation included the number of root galls, number of egg masses, number of eggs per egg mass, and nematode population in 300 g of soil. Data were analyzed using analysis of variance followed by DNMRT test at a 5% significance level. Results: The results showed that only the Trichoderma sp. isolate from Salimpaung significantly (p<0.05) suppressed the soil nematode population, with an effectiveness of 45.36% compared to the control. For the parameters of root gall number, egg mass number, and number of eggs per egg mass, no significant differences were observed between any of the Trichoderma isolates and the control. Conclusions: The Trichoderma sp. isolate from Salimpaung has potential to be developed as a local biological control agent to suppress Meloidogyne spp. populations in the soil.